The effect of perception of organizational politics on professionals’ engagement: the moderating role of the psychological safety climate - Chinelato, R. (2020)
The purpose of this research was to empirically test the hypothesis that the organizational psychological safety climate and the perception of organizational politics predict the extent to which employees feel engaged in their work. Using hierarchical linear modelling and data collected from 1,244 employees in 64 organizations, organizational level psycho-logical safety climate and employee-level perception of organizational politics predicted employee work engagement. There was also an unexpected significant cross-level interaction so that the negative effect of the perception of organizational politics was amplified in organizations with a positive psychological safety climate. In other words, organizational psychological safety benefits the work engagement of individuals more when they perceive the existence of low organizational politics. The results offer insight into the mechanisms by which the perceived organizational context may influence employees‟ work engagement and highlight the importance of the perceived organizational consistency in the promotion of work engagement within their organization.